Tinjauan Yuridis Permufakatan Jahat Penyalahgunaan Narkotika Berdasarkan Undang-Undang No : 35 Tahun 2009 Tentang Narkotika (Studi Putusan Nomor : 423/Pid/2018/PN. Mdn) - Agus Pranata Sinaga; Anggreini Atmei Lubis; Riswan Munthe (JUNCTO: Jurnal Ilmiah Hukum, 2019)
The narcotics problem has now penetrated all elements of the nation ranging from children to adults, from the lower classes to officials, even politicians and law enforcement are not sterile from narcotics abuse, so that eradication efforts are not enough to only be handled by the government and law enforcement officials instead, it needs to involve the whole community to play a role and actively participate in its prevention and eradication. This type of research is empirical juridical law research. Application of Material Criminal Law by the Judge against the Narcotics Misuse Act of Group I in non-plant form Decision number 423 / pid.sus / 2018 / PN. Mdn is right. In article 114 Paragraph (2) Jo Article 123 of the Republic of Indonesia Law NO: 35 of 2009 concerning Narcotics indicted in the Primair Indictment. The legal consideration by the Judge regarding the criminal acts of Misuse of Narcotics of Group I in the form of non-plants in imposing convictions is appropriate because the Judge in case Number 423 / pid.sus / 2018 / PN. Mdn handed down convictions based on witness statements, defendant statements, and documentary evidence according to Article 184 of the Criminal Procedure Code as legal evidence.